Fatty acids Profile, Nutritional Values, Anti-diabetic and Antioxidant Activity of the Fixed Oil of Malva parviflora Growing in Egypt - Heba Abd-Elhady El-gizawy; Mohammed Abdalla Hussein (International Journal of Phytomedicine, 2015)
In the current study, the fixed oil obtained from Malva parviflora seeds was tested for its physicochemical properties, fatty acids composition and nutritional value. The oil yield from the seed was 3.3%. The fatty acid composition was represented by 9 compounds, among which coriolic acid was the major fatty acid (31.60%), followed by pentadecanoic acid (30.05%). The antidiabetic and antioxidant activity of Malva parviflora seeds fixed oil (MPO) were also assessed. Diabetic rats were induced by injection of STZ (55mg/kg, i.p.) and diabetes was confirmed 48h after induction, and then allowed for 7 days to stabilize blood glucose level. MPO (1/100 LD50; 157mg/kg.b.w. and 1/50 LD50; 314mg/kg.b.w) was administered daily for 28 days. Treated diabetic rats significantly reduced elevated blood glucose, TC, TG, LDL-C, hepatic and renal TBARs and HP levels. The treatment also resulted in improved plasma insulin, HDL-C and GSH, SOD and CAT levels. These results clearly suggest that MPO may effectively normalize the impaired antioxidant status in streptozotocin induced diabetes as well as exert rapid protective effects against lipid peroxidation and ultimately reduce the risk of liver and renal complications.